2006
DOI: 10.1103/physrevlett.97.218301
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Exponent and Kuhn Length of Pinned Polymers by Single Molecule Force Spectroscopy

Abstract: The end-to-end distance and the contour length of single polymers in dynamic adsorbate layers were measured with a mechanical approach. Individual polysaccharide chains were covalently pinned to the surface with one segment and picked up randomly with an atomic force microscope tip. The polymer section between pinpoint and the pickup point was stretched by retracting the tip from the surface. The pinpoint was derived by measuring the normal force while laterally scanning the surface at constant height. For car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 36 publications
1
50
0
Order By: Relevance
“…However, it has been shown that deviation of the pulling direction from the normal direction to the surface induces systematic error in the measured forces of molecular events. 41,42 The off-normal pulling geometry is illustrated in Figure 4A. The apparent rupture forces detected in such geometry are expected to be higher than in the ideal geometry.…”
Section: 39mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been shown that deviation of the pulling direction from the normal direction to the surface induces systematic error in the measured forces of molecular events. 41,42 The off-normal pulling geometry is illustrated in Figure 4A. The apparent rupture forces detected in such geometry are expected to be higher than in the ideal geometry.…”
Section: 39mentioning
confidence: 99%
“…The apparent rupture forces detected in such geometry are expected to be higher than in the ideal geometry. 41,42 The average PDF that includes effect of the offnormal pulling as a function of an apparent rupture force F a can be calculated as Here we integrate over all possible lateral offsets and assume that rupture occurs when the tether is stretched at an extension that is close to the tether contour length L c ; factor…”
Section: 39mentioning
confidence: 99%
“…Because the adsorption force between the polymer and the substrate is the weak van der Waals interactions, the polymer molecules are found to have high in-plane lateral mobility. [14] When the rate of the polymer chain movement exceeds the scanning speed of the instrument, visualization of the molecules is difficult and the imaging resolution may suffer. Also problematic is the in situ experiment under fluidic conditions where the solvent may easily remove the weakly attached molecules from the substrate.…”
Section: Immobilization Of Single Polymer Moleculesmentioning
confidence: 99%
“…Frequently the polymer is attached at its end thus giving the precise location of the attachment point on the polymer. Conventional coupling chemistries can be adopted to immobilize single polymers, for example, the immobilization of carboxyl-containing polysaccharides on amine-functionalized glass slides through amide formation, [14] poly(vinyl amine) on epoxyfunctionalized surfaces giving β-hydroxyalkylamine, [26] chloroterminated poly(dimethylsiloxane) on silicon oxide surface by way of a base-catalyzed nucleophilic substitution reaction. [13] The reactions of silanes with oxides or thiols/ disulfides with gold or silver (Figure 2a) are also frequently used to prepare covalently immobilized single polymers on these popular substrates.…”
Section: Immobilization Of Single Polymer Moleculesmentioning
confidence: 99%
See 1 more Smart Citation